Mengukur Kondisi Kesehatan Keuangan Perusahaan Sub- Industri Farmasi Saat Pandemi Covid-19 - Setiadi Alim Lim (Program Studi Manajemen, Fakultas Bisnis & Akuntansi, Universitas Katolik Musi Charitas, 2023)
This research is intended to obtain information regarding the financial health of companies in the pharmaceutical sub-industry (code F211) on the Indonesia Stock Exchange (BEI) during the period during the Covid-19 pandemic (2020-2022). To detect whether a company is experiencing financial health problems or its finances are experiencing pressure, a multiple discriminant analysis (MDA) model is used. There are 6 MDA models used, namely: Altman model, Fulmer model, Grover model, Springate model, Taffler model, and Zmijewski model. The type of research carried out includes exploratory descriptive research. The entire population was taken as a sample, namely 11 companies belonging to the pharmaceutical sub-industry (code F211). The research results show that the use of different models produces the same results, but some also produce different results. Generally, the results of analysis of a company experiencing very severe financial pressure using several models will produce the majority of the same results. Likewise, if an analysis is carried out on a company with a very healthy financial condition using several models it will produce the same results as the majority of the models used. The research results show that there are 4 companies that need to pay attention to their financial health, namely: PT Indofarma Tbk. (INAF), PT Kimia Farma Tbk. (KAEF), PT Phapros Tbk. (PEHA), and PT Pyridam Farma Tbk. (PYFA). There are 2 companies that are indicated to have very healthy financial conditions, namely: PT Kalbe Farma Tbk. (KLBF) and PT Industri Jamu and Pharmacy Sido Muncul Tbk. (SIDO).